An entrepreneur's social capital and performance. The role of access to information in the Argentinean case - Fornoni, Mariel (2012)
Purpose - The aim of this paper is to analyze the impact of an entrepreneur's social capital on their access to information, and how such access improves the performance of their entrepreneurial project. Design/methodology/approach - A Structural Equations Model (SEM) is estimated and validated from a database including information from 282 Argentinean entrepreneurs who answered a questionnaire specifically designed for this research. The analysis of this model allowed us to determine the impact of dependent latent variables on the performance of the start-up. Findings - The performance of an entrepreneurial project depends on an entrepreneur's access to finance, markets and information. Specific dimensions of social capital facilitate access to these resources: the relational dimension facilitates access to information; the resources dimension makes access to finance easier; the structural dimension helps the entrepreneur to access markets. Research limitations/implications - The sample is not large enough to analyze differences among specific types of entrepreneurial projects: for instance, the role of social capital in industrial and service entrepreneurship (activity sector), the differences between the federal capital, Buenos Aires, and the rest of the country (location), and between female and male entrepreneurs (gender). Originality/value - Our results help to understand which dimensions of an entrepreneur's social capital facilitate access to information and how these specific dimensions enhance the performance of their project. Hence, this paper has managerial and policy implications for generation of dynamic entrepreneurial projects capable of becoming development drivers.